2014
DOI: 10.1074/jbc.m114.574996
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively Oxidized CXXC Motifs within the CD3 Heterodimeric Ectodomains of the T Cell Receptor Complex Enforce the Conformation of Juxtaposed Segments

Abstract: Background: CD3 subunits are essential signaling components of the TCR. Results: The membrane proximal CD3 CXXC motif is constitutively oxidized and critical for subunit conformation. Conclusion: The CXXC intramolecular disulfide bond is an important structural feature of the CD3 subunits that couples extracellular activating events to intracellular signaling regulation. Significance: Redox characterization provides insight into CD3 rigidifying elements in mechanotransduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
3
21
0
Order By: Relevance
“…1 D-F and 3C). The TCR and CD3 ECD-TM domain "connecting peptides" are highly conserved and affect TCR-CD3 function when altered (32)(33)(34)(35)(36)(37). Given the longer length of the TCR connecting peptides relative to the CD3 connecting peptides, there is sufficient space for the TCR to be placed over the CD3 ECDs, consistent with what was observed for our pMHC-TCR-CD3 complexes (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…1 D-F and 3C). The TCR and CD3 ECD-TM domain "connecting peptides" are highly conserved and affect TCR-CD3 function when altered (32)(33)(34)(35)(36)(37). Given the longer length of the TCR connecting peptides relative to the CD3 connecting peptides, there is sufficient space for the TCR to be placed over the CD3 ECDs, consistent with what was observed for our pMHC-TCR-CD3 complexes (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Our data provide a structural framework that can potentially begin to reconcile disparate observations about how the TCR relays a ligation event to signaling. Such observations include studies showing that monomeric pMHC possesses little to no ability to induce signaling regardless of affinity (49), there exist signaling-permissive and -nonpermissive pMHC-TCR docking geometries (48), conformational changes occur in the TCR upon pMHC ligation (46,(50)(51)(52), the CD4 and CD8 coreceptors are required to place Lck relative to the CD3 ITAMs (53, 54), phosphatases are occluded from the T-cell Ag-presenting cell synapse (18,26,55), and mechanotransduction appears to be important for TCR signaling (19,36,(56)(57)(58)(59) (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, CD3 would be situated between the TCR and T cell membrane, which is consistent with the greater length of the TCR ␣ and ␤ chain stalk regions (21 and 16 residues, respectively) than those of CD3⑀␥ and CD3⑀␦ (each ϳ9 residues). Mutational studies have demonstrated the importance of these highly conserved stalks for the assembly and function of the TCR-CD3 complex (41)(42)(43)(44)(45). Extension of our NMR analysis to the MS2-3C8 ␣ chain will define the docking site for CD3 ECDs on the TCR more completely.…”
Section: Discussionmentioning
confidence: 99%
“…Ligation impacts disposition and function of the associated CD3 dimers (CD3 γ, CD3 δ, and CD3ζζ) as well as the transmembrane domains of the TCR heterodimer and CD3 subunits that interdigitate in the membrane to signal into the cytoplasm (8,9). A cascade of intracellular events involving phosphorylation of immunoreceptor tyrosine-based activation motifs (ITAMs) on the CD3 cytoplasmic domains with subsequent ZAP70 activation and downstream signaling follows (10,11).…”
mentioning
confidence: 99%